The most common bacteria isolated from Neonatal Intensive Care Unit at Baghdad Teaching Hospital/ Medical City - Abdul-Zahra Ali, Aqeela; Abdul-Jabbar Habib, Intesar (International Journal of Psychosocial Rehabilitation, 2020)
The present study is interested in the detection of the most common bacteria that contaminate the Neonatal Intensive Care Unit at Baghdad Teaching Hospital/Medical City; therefore, a total of 150 swab samples were collected from many inanimate objects (equipment and surfaces) at the Neonatal Intensive Care Unit (NICU) during the period from Aug. to Oct. 2019. All swab samples were cultured on routine culture media and incubated at 37 ºC for 24 hrs. 53 (35.33%) out of 150 (100%) swab samples gave positive culture, and the isolates were identified by traditional microbiological methods including morphological and microscopical characteristics and biochemical tests of the API system. The study provides evidence that the most common bacterial species that contaminate the inanimate objects (equipment and surfaces) at NICU/Baghdad Teaching Hospital were Pseudomonas aeruginosa and Klebsiella pneumoniae. E. coli, Enterobacter sakazaki, Acinetobacter baumannii, Bacillus spp., and Staphylococcus epidermidis.